Helicobacter pylori infection and body mass index in adolescents - Pereira, Carlos (2015)
Introduction: Recent studies have revealed an association between overweight and obesity and the risk of Helicobacter pylori (HP) infection. The aim of this study was to quantify the association between overweight and obesity and the risk of developing HP infection in a sample of portuguese adolescents. Methods: A sample of 447 adolescents aged 12 to 18 years old, attending a public school in Sátão, Portugal, was enrolled in this cross-sectional study. A self-administered questionnaire with questions about socio-demographic aspects, risk behaviours and daily habits was answered by adolescents.The adolescents were screened for HP infection using the 13C-urea breath test that consists in the exhalation of carbon dioxide in samples before and after swallowing urea labeled with non-radioactive carbon-13. Obesity was evaluated by the body mass index (BMI) calculated by the ratio of weight and height (Kg/m2), according to the Cole et al. tables. Prevalence was expressed in proportions and compared by the chi-square test. Crude odds ratio (OR) with 95% confidence intervals (CI) were used. Results: The prevalence of overweight and obesity was 13.0% and 1.6%, respectively. The prevalence of HP infection was 35.9%. Overweight and obesity was not associated with gender (male, OR=0.9 95%CI=0.5-1.6), age (>15 yrs, OR=1.3 95%CI=0.7-2.3), father´s professional situation (unemployed, OR=1.8 95%CI=0.8-4.1) smoking habits (yes, OR=0.7 95%CI=0.4-1.4), alcohol consumption (yes, OR=1.0 95%CI=0.5-2.0) and soft drink consumption (yes, OR=1.2 95%CI=0.4-3.4). However, overweight and obesity was associated with parents`educational level (< 9th grade, OR=2.1 95%CI=1.2-3.8), residential area (rural, OR=1.6 95%CI=1.1-2.8) and coffee consumption (yes, OR=1.7 95%CI=1.2-2.9). After adjustment by non-conditional logistic regression for gender, age, parents´educational level, father´s professional situation, residence area and coffee consumption the HP infection is not associated with overweight and obesity (OR=1.4 95%CI=0.8-3.2). Conclusions: Overweight and obesity in adolescents is associated with socio-demographic variables and addictive habits, but not with HP infection.